2016
DOI: 10.1016/j.rse.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing surface-soil moisture from the SMOS mission and the ORCHIDEE land-surface model over the Iberian Peninsula

Abstract: The aim of this study is to compare the surface soil moisture (SSM) retrieved from ESA's Soil Moisture and Ocean Salinity mission (SMOS) with the output of the ORCHIDEE (ORganising Carbon and Hydrology In Dynamic EcosystEm) land surface model forced with two distinct atmospheric data sets for the period 2010 to 2012. The comparison methodology is first established over the REMEDHUS (Red de Estaciones de MEDición de la Humedad def Suelo) soil moisture measurement network, a 30 by 40. km catchment located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 43 publications
3
52
1
2
Order By: Relevance
“…This study follows the comparison between modelled and retrieved SSM (Polcher et al, 2016) and attempts to elucidate whether the difference found can be attributed either to the retrieval algorithm, which converts TBs into estimated SSM, or its modelled counterpart.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study follows the comparison between modelled and retrieved SSM (Polcher et al, 2016) and attempts to elucidate whether the difference found can be attributed either to the retrieval algorithm, which converts TBs into estimated SSM, or its modelled counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Polcher et al (2016) show that temporal correlation measured between remotely sensed, in situ, and modelled SSM is mainly driven by the high-frequency behaviour of SSM. Therefore, this diagnostic is not very sensitive to the slower variations of the field studied.…”
Section: Comparison Analyses 321 Spatio-temporal Correlationmentioning
confidence: 99%
See 3 more Smart Citations